Phenotypic Heterogeneity in a Congenital Disorder of Glycosylation Caused by Mutations in STT3A. (May 2017) - Ghosh, Arunabha; Urquhart, Jill; Daly, Sarah; Ferguson, Anne; Scotcher, Diana; Morris, Andrew A. M.; Clayton-Smith, Jill
STT3A encodes the catalytic subunit of the oligosaccharyltransferase complex. A congenital disorder of glycosylation caused by mutations in STT3A has only been reported in one family to date, associated with a Type I congenital disorder of glycosylation pattern of transferrin glycoforms. The authors describe a further 5 related individuals with a likely pathogenic variant in STT3A, 2 of whom also had variants in TUSC3 . Common phenotypic features in all symptomatic individuals include developmental delay, intellectual disability, with absent speech and seizures. Two individuals also developed episodic hypothermia and altered consciousness. The family were investigated by autozygosity mapping, which revealed both a homozygous region containing STT3A and, in addition, a homozygous deletion of TUSC3 in one child. A likely pathogenic variant in STT3A was confirmed on Sanger sequencing of all affected individuals: the authors discuss the molecular findings in detail and further delineate the clinical phenotype of this rare disorder.